Exploring Internal Reverse Migration Patterns in Cumilla District, Bangladesh: A Case Study During the COVID-19 Pandemic - Minhazur Rahman Rezvi; Mr Nuruzzaman; Bayezid Khan; Shuhail Hussain; Mahmud Hasan Mahim (UIN Sunan Gunung Djati, 2024)
The study possesses two-fold objectives: first, to explain the nature of internal reverse migration in Bangladesh during the COVID-19 pandemic, and second, to explore the push-pull factors of it. This study used a qualitative analysis tool and conducted 04 case studies and 10 In-depth interviews of reverse migrants for case study-based analysis. the study found that the pandemic triggered the reverse migration of informal workers, particularly female workers. Livelihood crisis, food insecurity, unexpected shocks, health insecurity, low living costs, and fear of infection are push-pull factors of reverse migration during COVID-19. Furthermore, these push-pull factors have motivated informal workers to migrate from urban to rural areas during COVID-19. The findings recommend that policymakers should address the vulnerability of informal workers in policy decisions. Policymakers should introduce new programs, i.e., social protection, and emergency economic schemes to provide support to the informal workers during emergencies like COVID-19.